2023
DOI: 10.3389/fpls.2023.1181039
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the crop epigenome: a comparison of DNA methylation profiling techniques

Abstract: Epigenetic modifications play a vital role in the preservation of genome integrity and in the regulation of gene expression. DNA methylation, one of the key mechanisms of epigenetic control, impacts growth, development, stress response and adaptability of all organisms, including plants. The detection of DNA methylation marks is crucial for understanding the mechanisms underlying these processes and for developing strategies to improve productivity and stress resistance of crop plants. There are different meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 290 publications
0
3
0
Order By: Relevance
“…The numbers of m CG-DMCs with increased methylation levels in ungraft TK vs PT were higher than in ungraft TK vs TT (Table 4 ). This indicated that grafting affected methylation levels by influencing probably the activities of domains rearranged methyltransferase 1 (DRM1) and (DRM2) and directed by small interfering RNAs (siRNAs) (Erdmann and Picard 2020 ; Agius et al 2023 ). Differences in the numbers of m CG + m CHG-DMCs among three gene elements were studied, and results revealed that among the gene elements, UPS regions contained the highest numbers of m CG + m CHG-DMCs, followed by DWN regions but the lowest numbers were observed in GB regions (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The numbers of m CG-DMCs with increased methylation levels in ungraft TK vs PT were higher than in ungraft TK vs TT (Table 4 ). This indicated that grafting affected methylation levels by influencing probably the activities of domains rearranged methyltransferase 1 (DRM1) and (DRM2) and directed by small interfering RNAs (siRNAs) (Erdmann and Picard 2020 ; Agius et al 2023 ). Differences in the numbers of m CG + m CHG-DMCs among three gene elements were studied, and results revealed that among the gene elements, UPS regions contained the highest numbers of m CG + m CHG-DMCs, followed by DWN regions but the lowest numbers were observed in GB regions (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It also utilizes two anchoring enzymes ( Nsi I and Pst I) to capture more diverse restriction fragments, therefore providing a better overview of methylation sites across the genome. While it provides interesting elements to the family of MSAP methods coupled with sequencing technologies, the CREAM approach also only focuses on CCGG sequences recognized by restriction enzymes, thus ignoring DNA methylation in CHG and CHH contexts, notably involved in the regulation of genes and transposons ( Agius et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These methods enable the identification of methylation patterns across the genome, elucidating how epigenetic modifications influence gene expression and contribute to biological diversity and complexity. Moreover, knowing the dynamics of DNA methylation helps in exploring the developmental processes, environmental adaptability, and evolutionary mechanisms of organisms to improve stress resistance and productivity of crop plants [33]. Thus, the development and refinement of DNA methylation detection technologies continues to be a cornerstone of epigenetic research, with broad implications for biology and medicine.…”
Section: Methylation Detection Methodsmentioning
confidence: 99%